Chemical And Biological Studies Of Zingiber Phillipseae Rhizomes Extract - M. M., Yusoff; Tan, Wei Hsiang (IJPBS, India, 2012)
A novel flavonoidic compound, 3,5-dihydroxy-4’,7-dimethoxyflavone, has been isolated from the rhizomes of Zingiber phillipseae. The dichloromethane extract of this species was shown to be non-toxic with LC50 for acute and toxic levels at 9,732 ppm and 562ppm, respectively. The extract showed higher antioxidant activity than the standard (butylated hydroxytoluene, BHT) but lower than dichloromethane extract of Zingiber officinale. It showed significant activity against Staphylococcus aureus and Escherichia coli with minimum inhibitory concentration (MIC) at 200µg/ml and 225 µg/ml respectively. Both extracts were found negative toward Candida albicans.